Characterization of «solar» multicrystalline silicon by local measurements - Popov, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The features of local measurements of «solar» multicrystalline silicon (mc-Si) parameters are surveyed using examples of grain sizes, diffusion length of minority non-equilibrium charge carriers Ld and effective reflectivity of light R. It is revealed that the crystal grains in mc-Si have 4 groups of the reference sizes. The errors of the single local measurements of parameters are spotted. It is shown that the values of explored parameters are distributed under the normal law (the Gauss function). The algorithm to obtain the average values of mc-Si parameters with given precision is described. The used experimental procedures for the express non-destructive check of Ld and R in the mc-Si samples are briefly considered.